2012
DOI: 10.1056/nejmoa1106104
|View full text |Cite|
|
Sign up to set email alerts
|

Antenatal Thyroid Screening and Childhood Cognitive Function

Abstract: Background-Children born to women with low thyroid hormone levels have been reported to have decreased cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
377
3
22

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(414 citation statements)
references
References 18 publications
8
377
3
22
Order By: Relevance
“…However, comparison of women identified with TD during pregnancy and treated had statistically fewer adverse outcomes than women with TD who were not identified until after delivery and therefore not treated. On the other hand, the study by Lazarus et al (92) showed no benefit of T 4 treatment of SChypo pregnant women on their children, although study limitations discussed previously should be taken into account. Thus, it has been argued that until it is irrefutably demonstrated that T 4 treatment may prevent adverse obstetric outcomes, universal screening is not justified (102).…”
Section: Arguments Against Universal Screeningmentioning
confidence: 82%
See 1 more Smart Citation
“…However, comparison of women identified with TD during pregnancy and treated had statistically fewer adverse outcomes than women with TD who were not identified until after delivery and therefore not treated. On the other hand, the study by Lazarus et al (92) showed no benefit of T 4 treatment of SChypo pregnant women on their children, although study limitations discussed previously should be taken into account. Thus, it has been argued that until it is irrefutably demonstrated that T 4 treatment may prevent adverse obstetric outcomes, universal screening is not justified (102).…”
Section: Arguments Against Universal Screeningmentioning
confidence: 82%
“…In this sense, the most ambitious goal of universal screening for TD in the first trimester of pregnancy is to prevent irreversible situations and provide adequate amounts of iodine and T 4 to enable the brain of the fetus to develop in optimal conditions (88,89,90 This compares extremely favorably in comparison with other health problems in which screening is accepted, such as hypercholesterolemia or hypertension (31). The results of a study of antenatal thyroid screening and childhood cognitive function (92) indicated that T 4 treatment of pregnant women with SChypo or isolated hypothyroxinemia would bring no benefit to the children of these mothers compared with untreated mothers. Undoubtedly, this study is of great interest.…”
Section: Obstetric Complications Associated With Td "mentioning
confidence: 99%
“…Although no single factor during intrauterine development leads to psychiatric disorders in children, maternal thyroid hormone plays a major role in foetal brain development and is therefore implicated in the development of a range of offspring behavioural and psychiatric problems (16). This is supported by several research findings suggesting associations between early pregnancy thyroid disorders and cognitive development of offspring (6,17,18,19,20,21,22,23,24). There are however fewer studies investigating the potential relationship between maternal thyroid disorders during pregnancy and behavioural and psychiatric disorders in offspring at different ages, and no systematic reviews on the subject.…”
Section: Introductionmentioning
confidence: 90%
“…Published data on the prevalence of thyroid disease in pregnant women have been based on results of thyroid function tests and/or registration of hospital diagnosis and treatment. Studies with biochemical measurement of thyroid function have used stored serum samples collected as a part of routine prenatal programs (15,16), serum samples collected from women enrolled in a pregnancy cohort (17) or serum samples from women enrolled in a randomized trial (18). In such studies, the prevalence of disease depends on the biochemical definition of thyroid disease as well as the gestational week of sampling.…”
Section: Prevalence Of Thyroid Disease In Pregnancymentioning
confidence: 99%